Development of Student E-Worksheet Based on Guided Inquiry of Environmental Change Material to Train Science Process Skills for 10th Grade High School - Nabila Azahra; Herlina Fitrihidajati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
Abstract This research aims to produce an E-Worksheet based on guided inquiry of environmental change material to train students' science process skills that are theoretically and practically valid. This research used the 4-D development model; define, design, develop, and disseminate, but without the dissemination stage. The parameters in this study were the validity of the e-worksheet based on the validation results and the implementation of students' e-worksheet in terms of activity observation results and student responses. The targets or objects used in this study were 25 students of class X-14 SMA Al-Islam Krian. The research was conducted in December 2022 – June 2023. The research instruments used validation sheets, student activity observation sheets, and response questionnaire sheets. Data collection techniques were validation techniques, observation techniques, and questionnaire methods. Data analysis was carried out quantitatively descriptively. The results showed that the e-worksheet was declared very valid, with a validity score of 3.8 based on theoretical validity. The implementation of the e-worksheet developed in terms of the results of student activities got a percentage score of 100% with a very good category. The results of students' responses to the e-worksheet were very positive, with a percentage score of 98.7%. Based on these results, the e-worksheet developed was valid and feasible. Keywords: E-worksheet, Guided inquiry, Science process skills, Environmental change material Abstrak Tujuan penelitian ini adalah menghasilkan E-LKPD berbasis inkuiri terbimbing materi perubahan lingkungan untuk melatihkan keterampilan proses sains peserta didik yang layak dan valid secara teori dan empiris. Penelitian ini menggunakan model pengembangan 4-D tanpa dilakukan tahap dissemination. Parameter yang diteliti meliputi validitas E-LKPD berdasarkan hasil validasi dan keterlaksanaan E-LKPD ditinjau dari aktivitas dan respon peserta didik. Sasaran atau objek yang digunakan pada penelitian ini yaitu 25 peserta didik kelas X-14 SMA Al-Islam Krian. Penelitian dilakukan pada bulan Desember 2022 - Juni 2023. Instrumen penelitian yang digunakan yaitu lembar validasi, lembar observasi aktivitas peserta didik dan lembar angket respon. Teknik pengumpulan data yaitu teknik validasi, teknik observasi, dan metode angket. Analisis data dilakukan secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa E-LKPD dinyatakan valid dengan skor validitas 3,8 kategori sangat valid. Keterlaksanaan E-LKPD yang dikembangkan ditinjau dari aktivitas peserta didik sebesar 100% kategori sangat baik, dan respon peserta didik terhadap E-LKPD sangat positif sebesar 98,7%. Berdasarkan hasil tersebut menunjukkan bahwa E-LKPD valid dan layak untuk diterapkan. Kata kunci : E-LKPD, Inkuiri terbimbing, Keterampilan proses sains, Perubahan lingkungan